E-Citizens. Toward a New Model of (Inter)active Citizenry. - Ronchi, Alfredo M (Springer, 2019)
This book explores a society currently being transformed by the influence of advanced information technology, and provides insights into the main technological and human issues and a holistic approach to inclusion, security, safety and, last but not least, privacy and freedom of expression. Its main aim is to bridge the gap between technological solutions, their successful implementation, and the fruitful utilization of the main set of e-Services offered by governments, private institutions, and commercial companies. Today, various parameters actively influence e-Services’ success or failure: cultural aspects, organisational issues, bureaucracy and workflow, infrastructure and technology in general, user habits, literacy, capacity or merely interaction design. The purpose of this book is to help in outlining and understanding a realistic scenario of what we can term e-Citizenry. It identifies today’s citizen, who is surrounded by an abundance of digital services, as an “e-Citizen” and explores the transition from their traditional role and behaviour to new ones. The respective chapters presented here will lay the foundation of the technological and social environment in which this societal transition takes place.
Keywords: Partizipation; Staat; Bürger; Beteiligungsmodell; Digitalisierung; Öffentliche Sicherheit; Datenschutz; Privatheit; Governance; E-Government